Puerperal Morbidities After Delivery in a Tertiary Care Referral Hospital of Nepal - Malla, Rosy; Manandhar, Reeta (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: : In a developing country like Nepal maternal morbidity in the post partum period is a major healthcare concern. This study aims to analyze the maternal morbidities in women following delivery at Shree Birendra Hospital. Methods: This is a prospective, observational, hospital based study, carried out at Shree Birendra Hospital from 13th August 2012 to 13th Feb 2016. Women who underwent delivery in Shree Birendra Hospital with subsequent morbidities within the study period were included in this study. The variables considered in this study were pattern of postpartum morbidities, age, parity, mode of delivery and average duration of hospital stay. Results: During the study period, a total number of 3407 deliveries were conducted in Shree Birendra Army Hospital. Out of these, 54 patients (1.58%) had postpartum morbidities. Puerperal sepsis was the most frequent diagnosis seen in 18 patients (33.3%), followed by surgical wound infection in 14 (25.9%) and secondary postpartum hemorrhage (PPH) in 10 (18.5%). Conclusion: Puerperal sepsis remains the most common cause of postpartum morbidity.